Curvas de custos marginais de abatimento de gases de efeito estufa no Brasil: Resenha e oportunidades de mitigaç\~ao - Ronaldo Seroa da Motta; Lilia Caiado Couto; Luiza Castro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– This text review the current studies marginal abatement cost curves (MACC) of greenhouse gases (GHG) for the Brazilian economy, in particular for the industrial sector. Studies on technology-based curves has drawn attention of researchers since they have shown a significant amount of negative-cost abatement potential that would motivated the debate on green economy since growth could then increase if they were applied. So we first present the review of the estimated curves for Brazil and, based on them, we make a sensitivity analysis of estimating parameters to discuss the negative cost options. Finally we conclude that, despite the existence of estimation biases, GHG mitigation in Brazil can take advantage of low and negative cost options.
Keywords: Q; Q5; Q6; 330; GHG abatement costs; brazilian economy; industrial sector; Treibhausgas; Umweltbelastung; Umweltkosten; Brasilien